A Two-Step Mechanism for Cell Fate Decision by Coordination of Nuclear and Mitochondrial p53 Activities - Tian, Xiao-Jun; Liu, Feng; Zhang, Xiao-Peng; Li, Jun; Wang, Wei (PLOS ONE, 2012)
The tumor suppressor p53 has a crucial role in the DNA damage response. Here, we proposed an integrated model of the p53 network and explored how the nuclear and mitochondrial p53 pathways are coordinated to determine cell fates after -irradiation in radiosensitive tissues. Using numerical simulations, we found that depending on the extent of DNA damage, cells may survive, commit apoptosis after cell cycle arrest, or undergo apoptosis soon after irradiation. There exists a large cell-to-cell variability in outcome because of stochasticity in the generation and repair of DNA damage as well as cellular heterogeneity. At the cell population level, there occur two waves of apoptosis: a fast wave mediated by mitochondrial p53 within three hours postirradiation, and a slow wave mediated by nuclear p53 after eight hours postirradiation. Thus, we propose a two-step mechanism for cell fate decision. The first step is to decide whether DNA damage is severe enough to trigger apoptosis directly through the mitochondrial p53 pathway, while the second step is to determine whether the damage is fixed after cell cycle arrest. Such a mechanism may represent an efficient and reliable control mode, avoiding unnecessary death or greatly promoting the execution of apoptosis. It was also demonstrated that nuclear p53 can inhibit the pro-apoptotic activity of mitochondrial p53 by transactivating p21, and Mdm2 can facilitate apoptosis by promoting the mono-ubiquitination of p53. These results are either in good agreement with experimental observations or experimentally testable. Our work suggests that both the transcription-independent and -dependent p53 activities are indispensable for a reliable choice of cell fate and also provides clues to therapeutic manipulation of the p53 pathway in cancer treatment.